Melt Procedure Affects the Photosynthetic Response of Sea Ice Algae - Campbell, Karley; Mundy, C. J.; Juhl, Andrew R.; Dalman, Laura A.; Michel, Christine; Galley, Ryan J.; Else, Brent E.; Geilfus, Nicolas X.; Rysgaard, Søren (Frontiers in Earth Science, 2019)
The accuracy of sea ice algal production estimates is influenced by the range of melting procedures used in studies to obtain a liquid sample for incubation, particularly in relation to the duration of melt and the approach to buffering for osmotic shock. In this research, ice algal photophysiology from 14C incubations was compared in field samples prepared by three melt procedures: i) a rapid ≤ 4 h melt of the bottommost (< 1 cm) ice algal layer scraped into a large volume of filtered seawater (salinity 27 - 30), ii) melt of a bottom 5 cm section diluted into a moderate volume of filtered seawater over 24 h (salinity 20 - 24), and iii) melt of a bottom 5 cm section without any filtered seawater dilution over about 48 h (salinity 10 -12). Maximum photosynthetic rate, photosynthetic efficiency and production at zero irradiance were significantly affected by the melt treatment employed in experiments. All variables were greatest in the highly diluted scrape sample and lowest in the bulk-ice samples melted in the absence of filtered seawater. Laboratory experiments exposing cultures of the common sea ice diatom Nitzschia frigida to different salinities and light conditions suggested that the field-based responses can be attributed to the rapid (< 4 h) adverse effects of exposing cells to low salinities during melt without dilution. The observed differences in primary production between melt treatments were estimated to account for over 60% of the variability in production estimates reported for the Arctic. Future studies are strongly encouraged to replicate salinity conditions representative of in situ values during the melting process to minimize hypoosmotic stress, thereby most accurately estimating primary production.